Sustaining Customer Loyalty Through Customer Engagement In Environmentally Friendly Brands: Study Of The Body Shop’s Social Media Purchase - Felicia Yuliana Halim*; Margaretha Pink Berlianto (Universitas Syiah Kuala, 2023)
This research is aimed to examine the significance of the dimension of customer towards customer satisfaction, trust, and customer loyalty. The environmentally friendly brand is popular nowadays. This study was done by quantitative research using a total of 198 samples. The samples were analyzed statistically using the PLS-SEM. The results show that conscious attention and social connection have no significance effect towards customer satisfaction. On the other hands, enthused participation, pro-environmental, pro-community have significant effect to customer satisfaction. This research shows that customer satisfaction has significant effect to trust. Customer satisfaction and trust also shows significant effect to customer loyalty.